A General Level of Geography of Canda Course for Grade Nine - Smees, John (My University, 1981)
This project identifies a segment of the secondary school population which, in the author's opinion, is being ill-served by present day geography curricula. A philosophical argument is put forward in Chapter One as a model for new and more appropriate learning expressions. This introductory chapter is followed by four chapters of prepared student activities and guidelines for their implementation. Suggestions for additional activities are also provided. Chapter Two "What Can I Do Well?" is a diagnostic series of activities considered fundamental in a geography course. Chapters Three, Four and Five present a Geography of Canada based on the concept of working from the known to the unknown. Consequently, the titles are, "Our Neighbourhood", "Choosing a Place to Live in Canada" and "Canada and the world". Although these three chapters constitute an entire course, most of the activities therein could be successfully incorporated into existing courses. General conclusions and other summary remarks are contained in Chapter Six.
Keywords: Geography; Geography